CHANGES IN THE HISTOARCHITECTONICS OF THE KIDNEYS IN POSTNATAL ONTOGENESIS DURING ALCOHOL INTOXICATION - Shukhrat J. Teshayev,; Izzat S. Khamroev , (Central Asian Journal of Medicine, 2023)
The results of the study showed that 30% of rats who consumed alcohol for 30 days developed an apoptosis ulcer in the kidneys. In 9-year-old squids who consumed alcoholic beverages for 120 days, morphological changes were observed in the kidneys, that is, in the podocytes located in the kidneys, which indicates a decrease in the expression of the Ki-67 marker during apoptosis. The proliferative activity of pathocytes is manifested in intercellular interactions.